The role of zinc sulphate as a retarder for alkali activated binders and its influence on the rheological, setting and mechanical behaviour. (15th August 2022) - Nedunuri, Aparna Sai Surya Sree; Muhammad, Salman
Highlights: ZnSO4 ·7H2 O is an effective retarder for delaying the setting of AASFA mixtures. ZnSO4 ·7H2 O increased the workable time of AASFA mortar but reduced their flow. AASFA mixtures with ZnSO4 ·7H2 O have attained more than 80% of the control strength. The network in AASFA with 3% of ZnSO4 ·7H2 O can be predominantly due to coagulation. Abstract: Alkali activated materials are alternative cementitious materials that have demonstrated good mechanical and durability properties. However, these materials exhibit quick setting and poor workable times. To address this issue, in this study, zinc sulphate was used as a retarder to alkali activated ground granulated blast furnace slag and fly ash (AASFA) mixtures. The rheological, setting and mechanical behaviour of AASFA mixtures with different molar modulus, proportion of fly ash and dosage of ZnSO4 ·7H2 O were investigated. Delay in setting time, increase in workable time, reduction in yield stress and apparent viscosity, and absence or minimal secondary increase in storage modulus of AASFA mixtures were observed with an increase in the dosage of ZnSO4 ·7H2 O from 0 to 3%. The compressive strength of AASFA mixtures at early ages decreased with an increase in the content of zinc sulphate and attained more than 80% of the control strength at 28 days and above.